Modern Language Quarterly: tomo 10 (1949), tomo 11 (1950), tomo 12 (1951), tomo 13 (1952). - Alatorre, Antonio (El Colegio de México, 1958)
Se reseñó: Modern Language Quarterly: tomo 10 (1949), tomo 11 (1950), tomo 12 (1951), tomo 13 (1952).